ANAPHYLATOXINS IN PRETERM AND TERM LABOR - Soto, Eleazar (2005)
OBJECTIVE: The complement system plays a central role in the first line of defense against invading pathogens, and its activation involves the release of potent pro-inflammatory mediators such as anaphylatoxins C3a, C4a and C5a. The aim of this study was to determine whether differences existed in maternal plasma anaphylatoxin concentrations between patients with term and preterm parturition. STUDY DESIGN: A cross-sectional study was designed to determine the plasma anaphylatoxin concentrations in 296 pregnant women in the following groups: 1) normal pregnancy between 20–36 6/7 weeks (n=64); 2) term not in labor (n=70); 3) term in labor (n=60); and 4) preterm labor with intact membranes (n=102). Women with preterm labor were classified into: a) term delivery (n=24); b) preterm delivery without intra-amniotic infection (IAI) (n=62); and c) preterm delivery with IAI (n=16). Concentrations of C3a, C4a and C5a were determined by ELISAs. Statistical analysis was conducted with non-parametric methods. RESULTS: 1) The median plasma C5a concentration was lower in women at term in labor than in those not in labor (p<0.001). In contrast, there were no differences in plasma C3a and C4a concentrations between the two groups (p>0.05). 2) Among patients with preterm labor, those with IAI had a higher median plasma C5a concentration than those without IAI and those who delivered at term (post-hoc tests p<0.001 and p=0.01, respectively). When comparing the preterm labor subgroups with normal pregnancy, only women with preterm delivery and IAI had a median plasma C5a concentration higher than that of normal pregnant women (Kruskal-Wallis p<0.001, post hoc test p<0.001) There was no difference in the plasma C4a concentration among patients with preterm labor. The median plasma C3a concentration in patients with preterm labor with IAI was significantly higher than in those without IAI (Kruskal-Wallis p=0.01, and post-hoc test p=0.005). There was no difference in the plasma C3a concentrations between women with preterm labor who delivered at term and those with preterm delivery, with or without IAI. In addition, no differences were observed in the median plasma C3a concentration between women with normal pregnancy and those in each of the preterm labor subgroups. CONCLUSIONS: The maternal plasma concentration of anaphylatoxin C5a is increased in women with preterm labor and IAI, but not in spontaneous labor at term.